Methodology for identifying the socio-economic genome on the commodity market for sugar production - D. Yu. Zhmurko (Вестник университета)
Sets of high probability cycles are determined, and also a common cyclic genome for the sugar industry is identified, which together affect the indicators of sugar, sugar beet, and sugarcane production. The regularities of the cyclical dynamics of large regional structures in the sugar industry are studied. For the first time in practice, the method of detecting the cyclic genome has been implemented not only by spectral analysis, but also by forward analysis (periodograms are built based on forward analysis). It is practically confirmed that the forward analysis when constructing periodograms shows results significantly better in than the classical spectral analysis. New patterns in the displacement (mutation) of the cyclic genome of the world sugar production are revealed. Sociogenetic patterns (cycles of different nature) are determined, for example, the cycle of a group of developed countries was 8.23 years, the cycle of developing countries – 8.39, the cycle of “Third world” countries – 7.6. A cyclical drift in world sugar production is revealed: after the end of World War II it shifted from the usual 9.49 years for the XIX century – the middle of the XX century to the current value of 7.12 years.